Management of pericoronitis for partial eruption of second permanent molar in a pediatric patient - Tengku Natasha Eleena binti Tengku Ahmad Noor; James Lian Yoon Chen; Mohd Safwani Affan Alli; Mohd Hosni bin Mahmood (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2021)
Background: This article discussed the management of pericoronitis for partial eruption of molar on pediatric patients. Purpose: This case report was to discuss how to manage a pediatric patient with a partially erupted second molar by using an electrosurgery method as the last alternative; also, it assessed whether or not the treatment facilitates spontaneous tooth eruption in respect to incomplete treatments. Case: A 9-years-old girl visited the Kuching Armed Forces Dental Clinic with her parents and complained of recurrent swelling on her lower right jaw in the last six months and noticed a tooth-like white lump under it. After a deliberate examination, the dentists came up with a diagnosis of pericoronitis because of a partially erupted second molar. Case Management: In managing a pediatric patient, a systematic desensitization was performed whereby the first visit was more of non-invasive treatment such as oral health instructions, a proper tooth brushing technique, and local scaling and debridement. Operculectomy using the electrosurgery had been carried out in the fourth visit and reviewed after one-week treatment that shows uneventful healing. Conclusion: To prevent and treat oral problems, it is imperative to develop child’s interest and willingness in using dental services. Hence, an early diagnosis is critical, especially as parents seek for the best treatment duration and treatment methods with the least number of consequences. The food impaction and the recurrent swelling because of pericoronitis have a major impact on the patient; therefore, treatment is provided regardless of patient’s age.